Technical and environmental assessment of forestry residues valorisation via fast pyrolysis in Ireland. (June 2023) - da Costa, Tamíris Pacheco; Murphy, Fionnuala; Roldan, Rocio; Mediboyina, Maneesh Kumar; Chen, Wenhao; Sweeney, Joseph; Capareda, Sergio; Holden, Nicholas M.
Abstract: The valorisation of forestry residues is gaining interest due to the increasing concerns over climate change and resource scarcity. They are considered important renewable resources of feedstocks to produce energy and other derived bioproducts. However, a holistic technical and environmental analysis of the valorisation of these residues via fast pyrolysis considering different forest residue alternatives and pyrolysis operational conditions is still lacking in the literature. For this reason, this study evaluated the production of bio-oil, synthesis gas and biochar using spruce, pine, and larch residues in three particle ranges and at three pyrolysis temperatures. Based on the experimental results, a virtual model was developed for the most appropriate forestry residues and operational conditions. The experimental process selected for further life cycle assessment (LCA) was the production of bio-oil from larch at a pyrolysis reaction temperature of 300 °C due to its superior bio-oil production. The results in the main impact categories presented better impact parameters than other conversion pathways found in the literature. However, the study likewise established one critical fact from adopting the pyrolysis process: the extensive heat energy requirements. The pyrolysis process is indeed relatively energy-intensive in terms of external heat consumption. However, syngas production could supply the conversion process's heat requirement by concurrent reuse. In addition, the excess energy in the form of biochar could offset the required electrical energy of the process. Hence, for the pyrolysis process to be sustainable, syngas energy must be used on-site, while biochar is used as co-firing fuel for electricity production. Graphical abstract: Image 1 Highlights: Bio-oil and syngas were produced via fast pyrolysis using forestry residues. Spruce, pine, and larch were tested at three pyrolysis temperatures. Virtual model was developed for the most appropriate conditions. The environmental performance was assessed through the LCA approach. The products generated can help to reduce social and environmental costs.